Filtering of Chest Compression Artefacts in the Electrocardiogram - Jekova I.; Krasteva V.; Dotsinsky I. (Bioautomation, 2009)
Long interruptions of cardiopulmonary resuscitation (CPR) in case of a sudden cardiac arrest result in higher failure rate of resuscitation. The current work concerns the filtering of the chest compression (CC) artefacts during CPR, which is essential for the CPR continuation during electrocardiogram (ECG) analysis by automated external defibrillators (AEDs). We have studied two possible approaches - one based on high-pass filter (HPF), and another using band-stop filter (BSF) with adjustable cut-off frequency. The purpose is to improve the quality of the signal provided to the ECG analysis module, aiming at a reliable decision to Stop CC if VF is present or to Continue CC for all other rhythms, including asystole (ASYS) or 'normal' rhythms with ventricular complexes (NR). The two filters are tested with artificially constructed ECG+CC signals, as well as with real ECGs recorded during CPR. The HPF passes the high-frequency components of the QRS complexes and effectively suppresses CC artefacts. This allows correct recognition of NR and ASYS. However, HPF suppresses the VF amplitude thus compromising the VF detection sensitivity. The BSF is favorable for detection of NR and VF but presents problems for ASYS detection because there are often attending residual high-frequency components belonging to the CC artefacts.